(untitled) (Journal of the College of Education for Women, 2019)
This study aims to show the markers of the Arabic noun(genitive, nun nation articles,vocative, definite article and predication). These markers distinguish the noun from otherparts of sentence. It alsoaims at showing why these markers are peculiar to nouns.